World processed food trade : a comparative analysis of New Zealand and selected exporters : a thesis presented in partial fulfilment of the requirements for the degree Master of Applied Economics in Agricultural Economics at Massey University - Smith, Hamish M (Massey University, 2000)
International trade in processed food products has been a dynamic component of world economic activity over the past twenty years, with the value of world processed food trade more than tripling between 1976 and 1996. Fueling this growth has been recent dietary trends towards higher-valued processed foods, which has been accelerated by rising incomes, urbanisation and demographic and socio-economic factors. In highly developed markets such as the European Union, North America and Japan, consumer ready processed goods make up a large and growing share of the food and agricultural imports. Consumer ready processed goods are also making inroads in developing countries as consumers demand convenience foods such as frozen 'ready-meals' and evening 'meal solutions.' Despite this, most agro-food trade research has been concentrated on the trade in bulk commodities (non-processed food products). This research evaluates the performance of New Zealand's processed food exports, relative to the performance of five other leading processed food competitors. Combined with revealed comparative advantage indices, a constant market share model is applied to the data to determine factors responsible for enhancing or retarding the performance of a focus country's processed food exports. An important empirical finding is that New Zealand's competitive position in international processed food markets deteriorated over the 1976-1996 period. A combination of declining competitiveness, reduced comparative advantage and a heavy reliance on traditional export markets has eroded New Zealand's share of world processed food trade. The failure to capitalise on the potential offered by Asian markets has also limited the growth of New Zealand's processed food trade. However evidence suggests that since the early 1990s New Zealand has been able to diversify into the fast growing Asian markets and is beginning to increase her competitiveness.
Keywords: Food industry; Trade; New Zealand